Stability indicating RP-HPLC method for simultaneous determination of gatifloxacin and dexamethasone in binary combination - Syed Naeem Razzaq; Muhammad Ashfaq; Islam Ullah Khan; Irfana Mariam; Syed Saleem Razzaq; Ghulam Mustafa; Muhammad Zubair (Universidade de São Paulo, 2017)
Abstract In this study, conditions were optimized for development of a simple RP-HPLC method for simultaneous analysis of gatifloxacin and dexamethasone in different matrices like pharmaceuticals, human serum and urine. Good separation of gatifloxacin and dexamethasone from the induced degradation products was accomplished using C8 as stationary phase; 0.02 M phosphate buffer (pH 3.0) and methanol (42:58 v/v) as mobile phase. The concentration was measured with DAD at 270 nm. Linearity was observed in the range of 0.000040-0.000280 mol/L for gatifloxacin (r2≥0.999) and 0.000013-0.000091 mol/L for dexamethasone (r2≥0.999). Both the analyte peaks were completely separated from the peaks of induced degradation products as indicated by the peak purity index (≥0.9999 for both analytes). The optimized method is recommended to be used for concurrent analysis of gatifloxacin and dexamethasone in different matrices.